Using persistent identifiers to track PhD outcomes - Madden, Frances; Bunakov, Vasily (Cadernos BAD, 2020)
The British Library and STFC are working together to connect metadata relating to PhD theses to use of research facilities provided by STFC. Through the creation of a graph which connects metadata across EThOS, the UK national e-theses repository, the STFC insitutional repository ePubs and the Diamond Light Source repository, links between the theses, authors and institutions have been made. This pilot work has the potential to be extended to enhance the metadata stored within EThOS which is administered by The British Library. This work presents an exciting possibility for other institutions as this graph will present a method to enable the bi-directional updating of metadata held across different systems.